Proteinuria in sarcoidosis: prevalence and risk factors in a consecutive outpatient cohort - Chopra, Amit; Brasher, Paul; Chaudhry, Haroon; Zheng, Robert; Asif, Arif; Judson, Marc A. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
Introduction: While sarcoidosis has been recognized as a potential cause of proteinuria, no study has systematically evaluated the prevalence and risk factors for proteinuria in sarcoid patients. Methods: Consecutive sarcoid patients followed in a university clinic were identified prospectively. All patients with spot urine protein-to-creatinine ratio (UPCR) between 11-2012 and 07-2015 were included in the analysis. Proteinuria was defined as a spot UPCR equal to or exceeding 0.3 mg/mg. The primary goal of the study was to determine the prevalence of proteinuria in this sarcoidosis cohort. Results: Our study cohort consisted of 190 sarcoidosis patients (65% female, 82% white, mean age of 53 years (range 24-88)). Proteinuria was present in 14/190 (7%) of this cohort. Only5/190 patients (2.5%) had proteinuria who did not have a risk factor for proteinuria. Estimating the 24-hour urine protein excretion by extrapolating from the spot UPCR, proteinuria was moderate in amount (mean 1.60, range 0.32-5.06 mg/mg). Proteinuric patients received a lower mean daily dose of corticosteroids compared to those without proteinuria (0 mg vs 4.7 mg of prednisone); however, this difference did not reach statistical significance (p = 0.20). Conclusion: Our study found proteinuria in 7% of the 190 sarcoid patients. More than half of the patients with proteinuria had a known risk factor for proteinuria other than sarcoidosis. Proteinuria is uncommon in sarcoidosis, and, when it occurs, it should not be assumed that sarcoidosis is the cause without investigating alternative causes of proteinuria.